Historical “gothic” novel in the context of English preromantic literature (Proceedings of Southern Federal University. Philology, 2015)
The article discusses the development of the Gothic historical novel in English literature of the last third of the XVIII century. Initial installation on a stylized medieval romance, and attempts to reconstruct historical color associated with the overall objective aesthetic and artistic development of the Middle Ages (“The Castle of Otranto” Mr. Walpole, 1764) is replaced by the rejection of the historical and geographical exoticism and transferring activities in a much closer historical Age (K. Reeve “Old English Baron”, 1777). Image of real historical figures and famous historical events was a major literary discovery of the historic Gothic novel (S.Li “Refuge, or Tale of other times”, 1785), is preceded in this regard in the work by W. Scott. The next conquest of Gothic historical novel was the desire to enter the historical events in a common “historiosophical” story, reflecting the unbreakable laws of nature (C. Reeve, “Memoirs of Roger de Clarendon,” 1793). A similar trend is a characteristic of educational tradition, and yet, the historic Gothic novel, opens the way to a romantic historical novel, with its nostalgia for bygone times, tragic conflicts, an ideal hero, carried along by fate historic flow. Formation of the genre is analyzed in the context of socio-political and literary-aesthetic discussions era.Keywords: gothic, novel, historical “gothics”, preromanticism, romantic, suggestion, didacticism, sentimental.Grigorieva Elena Valentinovna - candidate of linguistics, professor assistant of world literature theory and history dpt. Institute of philology, journalism and cross-cultural communication of Southern federal university. Phone: 8-903-404-35-60; e-mail: elval@sfedu.ru